Kielland’s Forceps: A Necessary Revolution? Ethical Dilemmas in Obstetrics and Gynaecology: Obstetrics and Gynaecology Essay Prize - Farrell, Robert (Trinity Student Medical Journal, 2018)
The Kielland’s forceps has been controversial since its inception. The unparalleled range of movement offered by its unique design made it for a time the instrument of choice for occipito-transverse arrest in the second stage of labour. In recent decades use of the Kielland’s forceps declined significantly following a series of damning case reports linking its use to significantly poorer neonatal outcomes, and now many obstetric trainees are not trained in Kielland’s deliveries. However, these case reports have never been replicated, and modern evidence now suggests that the not only is the Kielland’s forceps equivalent in neonatal and maternal outcomes to other forms of vaginal delivery for transverse arrest, but also that is significantly less likely to fail preventing the substantially poorer outcomes associated with sequential instrumentation, or emergency Caesarean section. The potential reintroduction of structured training in Kielland’s delivery raises ethical concerns regarding training related risk, and whether the profession has accurately quantified the potential risks involved. However, modern evidence broadly supports a positive balance of risk and favours the widescale reintroduction of the Kielland’s forceps.